Software development for fetal heart rate monitoring system - Mohd Rahimi bin Abd Rahman (2023)
There are six techniques of ECG enhancement, wnich are subtraction technique, correlation technique, cross-correlation technique, orthogonal basis, adaptive technique and linear combination methods.